Gender Roles in Understanding and Implementing Green Energy Technology in Indonesian Schools: Rasch Analysis - Ismail Ismail; Riandi Riandi; Ida Kaniawati; Wahyu Sopandi; Supriyadi Supriyadi; Suhendar Suhendar; Febrian Andi Hidayat (Qubahan Academic Journal)
This study aims to investigate gender differences in the understanding and application of green energy technology in schools in Indonesia. The method used is a survey with a questionnaire that covers aspects of knowledge attitudes readiness and obstacles related to green energy technology from a gender perspective. The sample of this study consisted of 829 teachers in various schools in Indonesia with a balanced distribution between male and female teachers. The data was analyzed using the Rasch measurement model with WINSTEPS 5.7.1 software to ensure the validity and reliability of the instrument. The results show that the instrument developed has good reliability and validity without significant item bias based on gender. The analysis shows that female teachers tend to have a higher understanding and application of green energy technology than male teachers. The ability distribution shows that most respondents are at a moderate to high level of ability in understanding and applying green energy technologies. These findings indicate the need for more inclusive and gender-sensitive education strategies to ensure all groups can contribute effectively to the implementation of green energy technologies in schools. The results of this study can be used as a basis for developing policy recommendations aimed at increasing equal involvement and understanding of green energy technologies among teachers both men and women. It is hoped that the gender gap in the understanding and application of green energy technology can be minimized and the application of this technology in schools can be improved.